Viability of Streptococcus mutans on transparent and opaque toothbrushes. - Spolidório, Denise Madalena Palomari [UNESP]; Goto, Emy; Negrini, Thaís de Cássia; Spolidório, Luis Carlos [UNESP] (My University, 2003)
PURPOSE: The objective of this study was to evaluate the viability of the microorganism Streptococcus mutans on toothbrushes made of opaque and transparent materials. METHODS: Twenty-eight toothbrushes (14 opaque and 14 transparent) were inoculated in tubes with brain heart infusion (BHI) broth of a standard strain of S. mutans and incubated in candle jars at 37 degrees C for 24 hours. Both the opaque and transparent toothbrushes were removed at T = 0 h (control); T = 0.5 h; T = 1 h; T = 2 h; T = 4 h; T = 8 h; and T = 24 h. Individual toothbrushes were subjected to agitation in a saline solution and samples of the solution were diluted and inoculated in Bacitracin Sucrose Agar--SB-20. RESULTS: After half an hour (T2) there was a significant decrease in the number of microorganisms on the transparent and opaque toothbrushes, respectively 6.0 x 10(5) and 9.4 x 10(5), when compared to the control. After the T3 = 1 hour, T4 = 2 hours, T5 = 4 h, the number of microorganisms decreased from 4.1 x 10(5); 2.1 x 10(5); 1.4 x 10(5); and 9.2 x 10(5); 5.7 x 10(5); 1.2 x 10(5) to zero (0.0) in T6 = 8 h, respectively on the transparent and opaque toothbrushes. The reduction in viable microorganisms was more obvious with the transparent toothbrushes, although the number of viable microorganisms was not significantly different for the two types of toothbrushes at the end of the experiment, T5 = 1.4 x 10(5) (transparent) and T5 = 1.2 x 10(5) (opaque). CONCLUSIONS: With both opaque and transparent toothbrushes, the number of microorganisms decreased with time. A reduction in the number of microorganisms on the transparent toothbrushes was observed following inoculation and incubation. This suggests the transparent toothbrushes inhibit the viability of the S. mutans.
Keywords: nylon; plastic; bacterial count; dental device; growth, development and aging; instrumentation; light; microbiology; Streptococcus mutans; tooth brushing; Colony Count, Microbial; Dental Devices, Home Care; Light; Nylons; Plastics; Toothbrushing